2015
DOI: 10.1039/c5ra02854j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of amino-functionalized poly(propylene carbonate)

Abstract: The first synthesis of amino-functionalized poly(propylene carbonate) (PPC) by terpolymerization of carbon dioxide (CO2), propylene oxide (PO), and N,N-dibenzyl amino glycidol (DBAG) following the removal of benzyl protecting groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Such aminofunctional polymers are a general precursor for postfunctionalized polycarbonates and for the attachment of proteins or drugs. They exhibit potential for medical devices, drug delivery systems, and in tissue engineering …”
Section: Functional Ethylene‐oxide‐based and Terminal Epoxide Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Such aminofunctional polymers are a general precursor for postfunctionalized polycarbonates and for the attachment of proteins or drugs. They exhibit potential for medical devices, drug delivery systems, and in tissue engineering …”
Section: Functional Ethylene‐oxide‐based and Terminal Epoxide Monomersmentioning
confidence: 99%
“…In the following, a brief summary of the classes of functional monomers that have been employed, will be given: (i) cyclohexene oxide derivatives; (ii) ethylene oxide derivatives; (iii) glycidyl ethers. In order to prevent side reactions, the functional groups in the monomers are often protected prior to polymerization, and the protective groups should be conveniently removed after polymerization, with no impact on the polycarbonate chains . Besides the use of functionalized monomers, the properties and functionality of aliphatic polycarbonates can also be controlled by the polymer architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, when functional groups are incorporated into the polymer backbones; the potential applications will be further broadened. For example, the introduction of hydroxyl, 6–9 carboxyl, 10,11 and amino groups 12–19 can effectively tunning the hydrophilic properties. Pendant functional groups may also provide active sites for further modification such as crosslinking, attaching bioactive substances to satisfy more specific applications 3,4,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous chemists have been looking for effective ways to improve PPC performance and enlarge its application fields. For example, different third monomer, such as lactone, N , N ‐dibenzyl amino glycidol, and lactide, has been introduced into the copolymerization of CO 2 and PO to produce block polymer. Wang et al reported a triblock copolymer of poly(allylglycidylether carbonate) (PAGEC)‐b‐PPC‐b‐PAGEC.…”
Section: Introductionmentioning
confidence: 99%